2022
DOI: 10.17305/bjbms.2022.7181
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of COVID-19 severity among pregnant patients

Abstract: Coronavirus disease 2019 (COVID-19) was declared a pandemic and has spread around the globe, unsparingly affecting vulnerable populations. Effective prevention measures for pregnant women, who are particularly affected, include early identification of those patients at risk of developing in-hospital complications, and the continuous improvement of maternal-fetal treatment strategies to ensure the efficient use of health resources. The objective of our retrospective study was to determine which patient biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
(93 reference statements)
1
3
0
Order By: Relevance
“…In the present study, no difference was found between the CRP levels of pregnant women hospitalized in the ward and ICU with and without COVID-19, similar to what was observed in Poland [34]. Among the maternal deaths recorded in the present study, most pregnant women had increased CRP values, which was also observed in Turkey [32] and in other studies [35].…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, no difference was found between the CRP levels of pregnant women hospitalized in the ward and ICU with and without COVID-19, similar to what was observed in Poland [34]. Among the maternal deaths recorded in the present study, most pregnant women had increased CRP values, which was also observed in Turkey [32] and in other studies [35].…”
Section: Discussionsupporting
confidence: 84%
“…Our study is one of the first to look at the association of vitamin D with adult mortality in the Polish population. Based on current knowledge, there are only a few published studies from Poland on vitamin concentrations in patients with COVID-19 ( 29 , 30 ). In the study by Ziuzia-Janiszewska et al.…”
Section: Introductionmentioning
confidence: 99%
“…( 29 ) found that, among others, obesity, comorbidities, higher levels of CRP, IL-6, creatinine, urea, and also lower eGFR value, albumin, calcium, and vitamin D concentration may be associated with poor COVID-19 outcomes. In another study from Poland, vitamin D concentrations were analyzed in 45 out of 52 pregnant women with confirmed SARS-CoV infection ( 30 ). It was shown that approximately 62% of pregnant women with COVID-19 had a decreased concentration of vitamin D (mean value – 27.15 ng/ml) ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation